Antagonistic potential of rhizosphere fungi against leaf spot and fruit rot pathogens of brinjal - Aktar, MT; Hossain, KS; Bashar, MA (Bangladesh Journal of Botany, 2015)
Antagonistic potentials of seven rhizoshere soil fungi viz., Aspergillus flavus Link., A. fumigatus Fresen., A. niger Tiegh., A. terreus Thom., Penicillium sp., Trichoderma harzianum Refat. and T. viride Pers. were tested in opposition to six pathogenic fungi viz., Colletotrichum sp., Curvularia lunata, Fusarium moniliforme, F. oxysporum, F. semitectum and Phomopsis sp. isolated from different leaf spots and fruit rots of brinjal. Out of seven soil fungi, Trichoderma harzianum was found most effective to control the growth of all the test fungi in the study of colony interactions and effects of volatile and non-volatile metabolites. This fungus may be exploited commercially to biocontrol the diseases. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21675 Bangladesh J. Bot. 43(2): 213-217, 2014 (September)